Determinación de los contaminantes producto de la combustión del parque automotor a gasolina en la parroquia San Buenaventura, ciudad de Latacunga, período 2015 - Veintimilla Martínez, Jessica Maribel (2016)
The study was conducted in San Buena Ventura Parish which belongs to Latacunga Canton in order to know in particular, the environmental pollution caused by motor gasoline cars that is one of the major causes of effects in human health and the causes of global warming, too. This research suggests a theoretical framework of environmental problems caused by vehicular pollution in urban areas; this is how the vehicle emissions become important issues in the world nowadays. So, the applicable law for gasoline vehicle sources is mentioned, establishing results based on the gas monitoring of exhaust gases from the vehicle through the use of the gas analyzer AVL DITEST, mentioning the most important: 32% of monoxide carbon, and 97.33% non-burnt hydrocarbon; these data were compared with the highest permissible limits by gasoline vehicle sources established by the Ecuadorian Technical Legislation NTE INEN 2204: 2002….